Analysis The Determinant of Financial Literacy Among Youth: A Bibliometric Study on Current Research and Future Directions - Irma; Refiana; Dimas; Muhammad; Vian; Septian (PROSENAMA, 2024)
Financial literacy is an important competency that enables individuals to make wise and sustainable financial decisions. Especially for the younger generation, financial literacy can be a strong foundation to face economic challenges in the future. This study aims to analyze the development and pattern of research on financial literacy for the younger generation through a bibliometric approach. This study uses a bibliometric analysis method to broadcast publications related to financial literacy for the younger generation. Data were collected from leading scientific databases such as Scopus which have been selected based on the year of publication. Bibliometric analysis shows a significant increase in the number of publications related to financial literacy for the younger generation over the past decade. The most frequently discussed topics include financial education, financial decision-making, and social influences on financial literacy. This study reveals that financial literacy for the younger generation is a global concern with significant growth in relevant literature. This study concludes that financial literacy for the younger generation is a rapidly growing field of research involving various disciplines. These findings can be the basis for the development of more effective educational policies and programs in improving the financial literacy of the younger generation worldwide.